2015
DOI: 10.1111/jvim.12589
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Placebo‐Controlled Clinical Trial of a Chewable Formulation of Amlodipine for the Treatment of Hypertension in Client‐Owned Cats

Abstract: BackgroundThere is an unmet clinical need for a cat‐specific formulation of amlodipine to treat hypertensive cats.ObjectivesTo assess the efficacy of chewable amlodipine tablets in reducing systolic blood pressure (SBP) in cats diagnosed with systemic arterial hypertension.AnimalsSeventy‐seven client‐owned cats with systemic hypertension were included (median age 14 years).MethodsThe study was randomized, double‐blinded, and placebo‐controlled. Forty‐two cats received 0.125–0.50 mg/kg amlodipine once daily for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 18 publications
5
42
0
Order By: Relevance
“…Hypertension is considered to cause harm by resulting in TOD, and decreasing QOL in these cats . Quality of life was found to be decreased in hypertensive cats before starting treatment in 1 study, and QOL was the most frequently reported reason for euthanasia in our study. Some clinical signs associated with CKD have been found to negatively impact QOL of cats with CKD .…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Hypertension is considered to cause harm by resulting in TOD, and decreasing QOL in these cats . Quality of life was found to be decreased in hypertensive cats before starting treatment in 1 study, and QOL was the most frequently reported reason for euthanasia in our study. Some clinical signs associated with CKD have been found to negatively impact QOL of cats with CKD .…”
Section: Discussionsupporting
confidence: 47%
“…This finding is consistent with most cats showing clinical signs of TOD at diagnosis. Earlier diagnosis of hypertension may decrease the number of cats presenting with evidence of TOD, as has been seen in a study that enrolled cats with lower blood pressure at diagnosis of hypertension, which may decrease the morbidity associated with the condition. In another study that performed regular blood pressure measurements longitudinally in initially normotensive cats, 52% were found to have evidence of TOD at the point at which they were diagnosed with hypertension, lower than the proportion of cats with TOD at time of diagnosis in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…1 The first reports on the use of amlodipine besylate for treatment of hypertension in cats were published in 1994, 3,4 and since then, two placebo-controlled clinical trials have been published. 5,6 Amlodipine is a second-generation dihydropyridine and exerts its effects by blocking L-type calcium channels in vascular smooth muscle. It binds and dissociates from its receptor fairly slowly, which accounts for the gradual onset and slow waning of effect.…”
mentioning
confidence: 99%
“…A glance through recent issues of the Journal of Veterinary Internal Medicine identifies prospective randomized clinical trials (RCTs) involving dogs,1, 2, 3, 4, 5, 6, 7, 8, 9 cats,10, 11, 12, 13 cows,14, 15 and horses16, 17 that cover the fields of neurology,1, 8 oncology,3, 5 cardiology,4, 6, 12 and internal medicine 2, 9, 10, 11, 13, 14, 15, 16, 17. Collectively, these findings suggest that we have entered into an era of prospective veterinary RCTs.…”
mentioning
confidence: 99%